Collective identities amid war and displacement: Syrians and Syrian refugees re‐imagine their country - Bachleitner, K (Wiley, 2021)
This article is interested in Syrian and Syrian refugees' ties of belonging to their country in times of war and displacement. By looking at individuals, the paper follows a micro-level approach to research societal ties of belonging to a country that has slipped into war. It argues that during conflicts, the meaning and boundaries of national identity are grasped in individuals' re-imagination of their country in either more “civic” or “ethnic” terms. As a result of this process, national identity may gain an inclusive, civic meaning based on the idea of citizenship or a more exclusive content based on the narrower confines of ethnicity and sect. Empirically, 100 Syrians and 100 Syrian refugees provided their vision of a future Syrian state in online interviews. The findings show that the majority of respondents' visions of Syria follows a civic rationale, with most survey participants linking their belonging to a future Syria with the broader ideas of citizenship, political rights and participation, rather than identifying the country in ethnic/sectarian terms. Combined with the theories, these results offer a glimpse into the societal formation of a new Syrian “we” amid an ongoing war and continuing waves of displacement.